Lipid Handling Protein Gene Expression in Colorectal Cancer: CD36 and Targeting miRNAs - Andrei Marian Niculae; Maria Dobre; Vlad Herlea; Florina Vasilescu; Laura Cristina Ceafalan; Bogdan Trandafir; Elena Milanesi; Mihail Eugen Hinescu (Life, 2022)
The reprogramming of lipid metabolism has been highlighted in colorectal cancer (CRC) studies, suggesting a critical role for the scavenger receptor CD36 and fatty acid synthase (FASN) in this malignancy. In this study, we analyzed the gene expression levels of CD36, FASN, the cell surface glypican 4 (GPC4), and the two transporters SLC27A3 and SLC27A4 in 39 paired tumoral and peritumoral tissues from patients with CRC compared with 18 normal colonic mucosae. Moreover, the levels of seven miRNAs targeting CD36 and most of the analyzed genes were evaluated. We found a significant impairment of the expression of all the analyzed genes except GPC4 as well as the differential expression of miR-16-5p, miR-26b-5p, miR-107, miR-195-5p, and miR-27a-3p in the colonic mucosa of CRC patients. Interestingly, CD36 and miR-27a-3p were downregulated and upregulated, respectively, in tumoral tissues compared to peritumoral and control tissues, with a significant negative correlation in the group of patients developing lymph node metastasis. Our results sustain the relationship between CRC and fatty acid metabolism and emphasize the importance of related miRNAs in developing new therapeutic strategies.